Diastema closure using direct bonding restorations combined with orthodontic treatment: a case report - Soon-Kong Hwang; Jung-Hong Ha; Myoung-Uk Jin; Sung-Kyo Kim; Young-Kyung Kim (Korean Academy of Conservative Dentistry, 2012)
Closure of interdental spaces using proximal build-ups with resin composite is considered to be practical and conservative. However, a comprehensive approach combining two or more treatment modalities may be needed to improve esthetics. This case report describes the management of a patient with multiple diastemas, a peg-shaped lateral incisor and midline deviation in the maxillary anterior area. Direct resin bonding along with orthodontic movement of teeth allows space closure and midline correction, consequently, creating a better esthetic result.